Syair "Mā Fī Al-Maqāmi Liz|i 'Aql Wa Z|i Adab" Karya Imam Syafi'i - Mochamad Sulthoni Faizin; Ayu' Atisah (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2019)
This study examines the poem "ma fi al-maqami lidzi‘aql wa dzi adab" by Imam Shafi'i in terms of Arudh and qawafi. Poem is an Arabic literary work that cannot be separated from the rules of Arudh and qawafi. If some poem violates the rules of Arudh and Qawafi then it can be agreed that poem is fasid (broken). Analysis in the science of Arudh will produce bahar, zihaf and ilah used in a poem. While qawafi science will produce qafiyah forms and types of qafiyah; this type of qafiyah is still further divided into three qafiyah letters, qafiyah societies and qafiyah rules. The method in this research is descriptive qualitative. Qualitative by examining the work of Shafi'i and descriptive imams for evaluating the results of the analysis of the poem "ma fi al-maqami lidzi‘aql wa dzi adab ".